Positive hepatitis B virus core antibody in HIV infection—false positive or evidence of previous infection?. Issue 2 (1st September 2014) - Pallawela, S. N. S.; Sonnex, C.; Mabayoje, D.; Bloch, E.; Chaytor, S.; Johnson, M. A.; Carne, C.; Webster, D. P.
<x xml:space="preserve">Abstract</x> Isolated HBV core antibody (anti‐HBc) is defined as the presence of anti‐HBc with a negative HBV surface antigen (HBsAg) and HBV surface antibody (anti‐HBs <10 IU/l). In patients infected with HIV with isolated anti‐HBc, the aim was to determine: The prevalence of isolated positive anti‐HBc; The most effective method of identifying which patients have had previous Hepatitis B Virus (HBV) infection; The prevalence of false positive anti‐HBc. HBV serology results were identified from 539 patients infected with HIV sampled between January 2010 and December 2012. In those with an isolated anti‐HBc and negative anti‐HBe, a second anti‐HBc test was carried out using a different assay. Samples were also screened for HBV DNA. The anti‐retroviral regimens at time of screening were documented. 101/539 had an isolated anti‐HBc. Of these, 32 (32%) had a positive anti‐HBe (including 1 equivocal) and 69(68%) were anti‐HBe negative. Of those negative for anti‐HBe, 32 were tested for both DNA and a second anti‐HBc. Of these 26 (81%) were on cART at time of HBV testing, with 25 (78%) on ART with anti‐HBV activity. The prevalence of isolated anti‐HBc was 19%. Only 32% were also anti‐HBe positive, whereas 97% of those anti‐HBe negative were positive on a second anti‐HBc assay suggesting lack of utility of anti‐HBe in resolving serological quandaries. One subject (3%) had a false positive anti‐HBc. There was no evidence of chronic HBV but 78% patients were on HBV‐suppressive combination anti‐retroviral therapy. J. Med. Virol. 87:208–212, 2015. © 2014 Wiley Periodicals, Inc.